2020
DOI: 10.1111/avsc.12511
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the invasion footprint:Ventenata dubiaand relationships to wildfire, environment, and plant communities in the Blue Mountains of the Inland Northwest, USA

Abstract: Questions: A recently introduced non-native annual grass, Ventenata dubia, is challenging previous conceptions of community resistance in forest mosaic communities in the Inland Northwest. However, little is known of the drivers and potential ecological impacts of this rapidly expanding species. Here we (1 identify abiotic and biotic habitat characteristics associated with the V. dubia invasion and examine how these differ between V. dubia and other problematic non-native annual grasses, Bromus tectorum and Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…In subplots where V. dubia was already established, community composition and biomass may have been influenced by the invader. In a previous observational field study, we found that V. dubia cover increased with decreasing Shannon Diversity (Tortorelli et al, 2020). However, whether diversity was reduced by invasion or diversity conferred invasion resistance was unknown.…”
Section: Experimental Design and Implementationmentioning
confidence: 81%
See 2 more Smart Citations
“…In subplots where V. dubia was already established, community composition and biomass may have been influenced by the invader. In a previous observational field study, we found that V. dubia cover increased with decreasing Shannon Diversity (Tortorelli et al, 2020). However, whether diversity was reduced by invasion or diversity conferred invasion resistance was unknown.…”
Section: Experimental Design and Implementationmentioning
confidence: 81%
“…Ventenata dubia had similar trait values to some resident species, including two introduced invasive annual grasses B. tectorum and B. arvensis, however these functionally similar graminoids were not abundant across the vegetation gradient, despite maintaining a scattered presence throughout the area for decades and heavily invading nearby Artemisia tridentata (big sagebrush) and burned forest communities (Johnson and Swanson 2005). This finding reflects the novelty of V. dubia's invasion into shallow soil communities in which few functionally similar native or introduced species have become abundant (Tortorelli et al, 2020). Furthermore, trait similarities to resident species suggest that standard below-and aboveground traits such as those we present here may not be driving V. dubia's relative success in these areas.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One study in shrublands identified a negative correlation between Ventenata dubia cover and native plant community richness and diversity and a positive correlation with annual forbs (Jones et al, 2018). In dry conifer forests, richness of annual forbs decreased with increased Ventenata dubia cover only in burned areas while richness of perennial forbs decreased in both burned and unburned areas (Tortorelli et al, 2020). Overall native plant richness and diversity were lowest in plots with high cover of Ventenata dubia in the Palouse and canyon grasslands regions (Jones et al, 2020), but the specific response of forbs was not examined.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanisms of hysteresis, and in particular how multiple redundant mechanisms act in concert, will provide important insights for ecosystem change on a global scale. At least 13 grass species initiate self-reinforcing feedbacks with fire in the U.S. (Fusco et al 2019;Tortorelli, Krawchuk, and Kerns 2020), and many more worldwide, including Australia (G. Miller et al 2010;Setterfield et al 2010), Brazil (Rossi et al 2014) and South Africa (Milton 2004). While the conversion of temperate forests and shrublands to grasslands may have a less per-hectare impact on carbon sequestration than tropical forests, the consequences are still relevant to the global carbon cycle, especially when forests (rather than the shrublands studied here) are replaced by herbaceous ecosystems (Kerns et al 2020).…”
Section: Global Impactsmentioning
confidence: 99%